2008
DOI: 10.1002/anie.200800144
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of P‐Stereogenic Alkynylphosphine Oxides by Rh‐Catalyzed [2+2+2] Cycloaddition

Abstract: Two plus two plus two: An enantioselective synthesis of P‐stereogenic alkynylphosphine oxides through a cationic rhodium(I)/modified‐binap complex catalyzed [2+2+2] cycloaddition of symmetrical dialkynylphosphine oxides with 1,6‐diynes was developed (see scheme; binap=2,2′‐bis(diphenylphosphanyl)‐1,1′‐binaphthyl, Z=CH2, O, or N‐sulfonamide). Furthermore, this method permits the synthesis of a C2‐symmetric P‐stereogenic bis(alkynylphosphine oxide).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(45 citation statements)
references
References 57 publications
0
45
0
Order By: Relevance
“…[26] The selective desymmetrization observed could be explained in terms of strong steric effects being present between the alkynyl group on the oxide and the phosphorus substituents of the chiral ligand before the final alkyne insertion in the corresponding rhodacyclopentadiene. Indeed, stereogenic phosphorus atoms are obtained as the result of the desymmetrization of symmetrical dialkynylphosphine oxides through a rhodium-catalyzed [2+2+2] cycloaddition pathway (Scheme 11).…”
Section: Miscellaneous Intermolecular [2+2+2] Cycloadditionsmentioning
confidence: 99%
“…[26] The selective desymmetrization observed could be explained in terms of strong steric effects being present between the alkynyl group on the oxide and the phosphorus substituents of the chiral ligand before the final alkyne insertion in the corresponding rhodacyclopentadiene. Indeed, stereogenic phosphorus atoms are obtained as the result of the desymmetrization of symmetrical dialkynylphosphine oxides through a rhodium-catalyzed [2+2+2] cycloaddition pathway (Scheme 11).…”
Section: Miscellaneous Intermolecular [2+2+2] Cycloadditionsmentioning
confidence: 99%
“…Preliminary studies have shown that these monophosphines are highly efficient ligands that either rival or outperform their biaryl-based counterparts in palladium-catalyzed Suzuki-Miyaura and Buchwald-Hartwig cross-couplings 50,51 , a host of gold(I)-catalyzed intramolecular cycloisomerizations [57][58][59] , as well as in the ruthenium-catalyzed direct ortho arylation of 2-phenylpyridine and N-phenylpyrazole with aryl chlorides 60 . In addition, biaryl monophosphines have also been prepared by rhodium-catalyzed [2 + 2 + 2] cycloaddition [61][62][63] and Diels-Alder cycloaddition extrusion 64 .…”
Section: Simon Doherty and Catherine H Smythmentioning
confidence: 99%
“…The cationic chiral rhodium(I)‐catalyzed cycloaddition was applied for desymmetrization of dialkynylphosphine oxide 83 with 1,6‐diyne 19 (entry 4) [18]. The P‐stereogenic alkynylphosphine oxide 84 was obtained in high yield and high enantiomeric excess.…”
Section: Construction Of Central Chiralitymentioning
confidence: 99%